Awareness and Knowledge of Hand Hygiene among Interns at a Tertiary Care Hospital – Questionnaire-Based Study - A, Ashiq; Preethi, V.; Dharmarajan, Dharmarajan; Ramula, Ramula; V, Sasikumar (Journal of Neonatal Surgery, 2025)
Background: Hand hygiene is globally recognized as a critical intervention in the prevention of healthcare-associated infections (HCAIs). Despite widespread awareness campaigns, compliance with hand hygiene practices among healthcare workers, particularly medical interns, remains suboptimal. Objectives: This study aimed to assess the level of awareness and knowledge regarding hand hygiene among Compulsory Rotatory Medical Interns (CRMIs) at a tertiary care teaching hospital, to identify areas of strength and weakness, and to determine the association between knowledge scores and variables such as gender, previous training, and department of posting. Methods: A cross-sectional questionnaire-based study was conducted over two months among 70 CRMIs using the WHO Hand Hygiene Knowledge Questionnaire for Health-Care Workers (2009 revision). Descriptive statistics, chi-square tests, and knowledge scoring systems were employed. Data analysis was performed using SPSS version 26. Results: Among the 70 participants, 64.3% had received formal hand hygiene training within the past three years. Knowledge scores were categorized as good (28.6%), moderate (50%), and poor (21.4%). Significant knowledge gaps were noted regarding the minimum recommended duration for alcohol-based handrub (42% correct) and the appropriate indications for handwashing versus hand rubbing (60% correct before clean/aseptic procedures). Conclusion: Although a moderate level of hand hygiene knowledge was observed among interns, gaps persist in crucial areas. Targeted, mandatory hand hygiene education, periodic assessments, and reinforcement at every clinical posting are recommended to bridge these gaps and enhance patient safety practices.